Porcine Reproductive and Respiratory Syndrome Virus Adapts Antiviral Innate Immunity via Manipulating MALT1 - Han Gu; Suya Zheng; Guangwei Han; Haotian Yang; Zhuofan Deng; Zehui Liu; Fang He (mBio, 2022)
ABSTRACT To fulfill virus replication and persistent infection in hosts, viruses have to find ways to compromise innate immunity, including timely impedance on antiviral RNases and inflammatory responses. Porcine reproductive and respiratory syndrome virus (PRRSV) is a major swine pathogen causing immune suppression. MALT1 is a central immune regulator in both innate and adaptive immunity. In this study, MALT1 was confirmed to be induced rapidly upon PRRSV infection and mediate the degradation of two anti-PRRSV RNases, MCPIP1 and N4BP1, relying on its proteolytic activity, consequently facilitating PRRSV replication. Multiple PRRSV nsps, including nsp11, nsp7β, and nsp4, contributed to MALT1 elicitation. Interestingly, the elevated expression of MALT1 began to decrease once intracellular viral expression reached a high enough level. Higher infection dose brought earlier MALT1 inflection. Further, PRRSV nsp6 mediated significant MALT1 degradation via ubiquitination-proteasome pathway. Downregulation of MALT1 suppressed NF-κB signals, leading to the decrease in proinflammatory cytokine expression. In conclusion, MALT1 expression was manipulated by PRRSV in an elaborate manner to antagonize precisely the antiviral effects of host RNases without excessive and continuous activation of inflammatory responses. These findings throw light on the machinery of PRRSV to build homeostasis in infected immune system for viral settlement. IMPORTANCE PRRSV is a major swine pathogen, suppresses innate immunity, and causes persistent infection and coinfection with other pathogens. As a central immune mediator, MALT1 plays essential roles in regulating immunity and inflammation. Here, PRRSV was confirmed to manipulate MALT1 expression in an accurate way to moderate the antiviral immunity. Briefly, multiple PRRSV nsps induced MALT1 protease to antagonize anti-PRRSV RNases N4BP1 and MCPIP1 upon infection, thereby facilitating viral replication. In contrast, PRRSV nsp6 downregulated MALT1 expression via ubiquitination-proteasome pathway to suppress the inflammatory responses upon infection aggravation, contributing to immune defense alleviation and virus survival. These findings revealed the precise expression control on MALT1 by PRRSV for antagonizing antiviral RNases, along with recovering immune homeostasis. For the first time, this study enlightens a new mechanism of PRRSV adapting antiviral innate immunity by modulating MALT1 expression.